Analysis of the Level of Basic Handball Skills of FIKK UNM Students - Achmad Karim; Ihsan Abbas (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aims to analyze the level of basic handball skills of students in the Physical Education, Health and Recreation Study Program (Penjaskesrek) FIKK UNM. This research is a quantitative descriptive study with a survey approach. The research population was all Penjaskesrek FIKK UNM students, with a sample of 30 students selected using purposive sampling technique. The research instrument used basic handball skill tests which included: (1) passing test, (2) catching test, (3) dribbling test, (4) shooting test, and (5) footwork test. Data analysis techniques used descriptive statistics in the form of percentages and categorization. The results showed that the level of basic handball skills of Penjaskesrek FIKK UNM students was in the category: very good 6.67% (2 students), good 23.33% (7 students), sufficient 40% (12 students), poor 20% (6 students), and very poor 10% (3 students). Overall, the level of basic handball skills of Penjaskesrek FIKK UNM students is in the sufficient category with a percentage of 40%. The analysis results per aspect show that shooting skills have the highest value (average 72.5), while footwork has the lowest value (average 58.3). The conclusion of this study is that the level of basic handball skills of Penjaskesrek FIKK UNM students still needs to be improved, especially in footwork and dribbling aspects.